Enhanced regulatory gene expressions in the blood and articular cartilage of patients with rheumatoid arthritis - Elena Vasilyevna Chetina; L A Semyonova; A L Logunov; V V Kolomatsky; M A Makarov; A A Roskidailo; E A Naryshkin; S A Makarov (Научно-практическая ревматология, 2012)
Objective: to study the expression ratio of the non-tissue specific regulatory genes mTOR, р21, ATG1, caspase 3, tumor necrosis factor-а (TNF-а), and interleukin-6 (IL-6), as well as matrix metalloproteinase 13 (MMP-13) and X type collagen (COL10A1), cartilage resorption-associated MMP13 and COL10A1 in the blood and knee articular cartilage in patients with rheumatoid arthritis (RA). Subjects and methods. Twenty-five specimens of the distal femoral articular cartilage condyles were studied in 15 RA patients (mean age 52.4+9.1 years) after endoprosthetic knee joint replacement and in 10 healthy individuals (mean age 36.0+9.1 years) included into the control group. Twenty-eight blood samples taken from 28 RA patients (aged 52+7.6 years) prior to endoprosthetic knee joint replacement and 27 blood samples from healthy individuals (mean age 53.6+8.3 years; a control group) were also analyzed. Real-time quantitative polymerase chain reaction was applied to estimate the expression of the mTOR, p21, ATG1, caspase 3, TNF-а, IL- 6, COL0A1, and MMP-13 genes. The levels of a protein equivalent in the p70-S6K(activated by mTOR), p21, and caspase 3 genes concerned was measured in the isolated lymphocyte lysates, by applying the commercially available ELISA kits. Total protein in the cell extracts was determined using the Bradford assay procedure. Results. The cartilage samples from patients with end-stage RA exhibited a significantly higher mTOR, ATG1, p21, TNFа, MMP-13, and COL10A1 gene expressions than did those from the healthy individuals. At the same time, IL6 gene expression was much lower than that in the control group. The expressions of the mTOR, ATG1, p21, TNFа, and IL 6 genes in the blood of RA patients were much greater than those in the donors. Caspase 3 expression did not differ essentially in the bloods of the patients with RA and healthy individuals. The bloods failed to show MMP-13 and COL10A1 expressions. High mTOR and p21 gene expressions were accompanied by the elevated concentrations of the corresponding proteins in the cell lysates of the patients with RA compared to the controls. Conclusion. The findings suggest for the first time that regulatory mTOR, ATG1, p21, and TNFа gene expressions are enhanced in the blood and articular cartilage of RA patients. These changes are accompanied by the increased expression of MMP 13 gene that is responsible for articular cartilage resorption. Therefore, the higher expression of the examined regulatory genes in the blood of RA patients may be indicative of articular cartilage degradation.